Gledal sem Disneya: Ob jubileju Guinnessovega rekorderja in začetnika animiranega filma v Mariboru Franca Kopiča (University of Maribor Press, 2022)
I Watched Disney: On the Occasion of the Jubilee of the Guinness Record Holder and Pioneer of Animated Film in Maribor, Franc Kopič. It is really strange and it is really fair to ask how the above three names appeared in the same context. The first started collecting phenomena and became famous after that, and the third got into the Guinness Book of Records because of the second. So the other two are also a phenomenon if they landed in the book of the first.